Shaping The Creative Activity of Future Specialists in Physical Education and Sports and Preparing Them for The Profession - Shanazarov Otabek Rahimdjonovich (Genius Publishing Group, 2023)
The article examines the process of shaping the creative activity of future specialists in physical education and sports and preparing them for their profession. The authors propose a conceptual model for organizing the educational process, which emphasizes the importance of integrating creative education with professional training. The authors argue that the ability to generate new ideas and approaches is critical for success in the ever-changing field of physical education and sports. The article highlights the importance of creating an environment that encourages creativity and innovation, providing students with the necessary tools and skills to develop and implement their ideas. The authors posit that successful implementation of this model requires a shift in the traditional approach to physical education and sports training, moving away from the focus on the acquisition of knowledge toward fostering critical thinking, problem-solving, and creativity.
Keywords: Athlete-centered approach; Health and wellness promotion; Inclusivity and diversity